(untitled) (Nepal Medical College Journal, 2019)
Corneal blindness is a major public health problem worldwide and infectious keratitis remains a leading cause. The aim was to analyze the microbial etiology of corneal ulcers and to determine the antibiotic susceptibility pattern of bacterial isolates. Among 84 clinically diagnosed cases, 33 (39.3%) were farmers by occupation. All cases were reviewed for predisposing conditions and clinical severity. Ulcers were categorized as mild in 49 cases moderate in 12 and severe in 23 cases. Predisposing conditions were detected in 65.5% (55/84) of patients. Forty-two cases showed culture positivity. Among these 42; 25 (29.7%) yielded fungi, 13(30.1%) yielded bacteria and the rest 4 (4.7%) showed mixed growth, accounting for a total of 29 cases showing fungal growth, and 17 demonstrating bacterial growth. Aspergillus spp. (10/29; 34.5%) were the commonest fungi and Staphylococcus aureus, (8/17; 47%) was the most common among bacteria. Majority i.e 66.7% (26 of 39) of those having trauma as the predisposing factor developed moderate to severe degree of corneal ulceration as compared to only 20% (9 of 45) of those without any history of trauma and this difference was found to be statistically significant (p<0.001). Interestingly, 20(68.9%) of 29 cases that yielded fungal growth on culture had previous history of ocular trauma in contrast to only 19 (34.5%) of 55 who had non-fungal keratitis (p=0.003). It was also observed that significantly higher number of fungal keratits cases exhibited pronounced degree of clinical severity, as compared to cases without any fungal aetiology (p<0.001) Topical administration of fourth generation fluoroquinolone eye drops remained the most effective drug of choice as far as the clinical outcome of bacterial keratitis was concerned. Trauma with vegetative matter predisposed to most cases of fungal keratitis. Severe form of ulceration was noticed in patients with fungal infection.